2018
DOI: 10.5755/j01.ms.24.1.17545
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Thermo-Treatment on the Physical and Mechanical, Color, Fungal Durability of Wood of Tectona Grandis and Gmelina Arborea from Forest Plantations

Abstract: This study evaluated the effect of thermo-treatment (THT) at 4 temperatures on the density, shrinking, mass loss, moisture absorption, color, durability in terms of resistance to decay, flexural strength, tensile adhesion of glue line and the infrared spectrum of the wood of Tectona grandis and Gmelina arborea. Sapwood, heartwood and radial and tangential grain patterns were studied. The results showed that the THT temperature decreases the density, the percentage of moisture absorption, the modulus of elastic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…For MOE, the 22% reduction was much higher than the 5% to 6% found by Menezes (2017), while Lengowski et al (2021) reported an increase of 24%. Finally, Méndez-Mejías and Moya (2018) reported the process had no significant effect on MOE even at 220°C, for both sapwood and heartwood.…”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations
“…For MOE, the 22% reduction was much higher than the 5% to 6% found by Menezes (2017), while Lengowski et al (2021) reported an increase of 24%. Finally, Méndez-Mejías and Moya (2018) reported the process had no significant effect on MOE even at 220°C, for both sapwood and heartwood.…”
Section: Resultsmentioning
confidence: 95%
“…For TMTW, reductions in MOR were also within the intervals reported in other studies with the same process and temperature, from 32% to 35% (Menezes 2017) to 50% (Lengowski et al 2021). For another process, Méndez-Mejías and Moya (2018) reported a 40% reduction in MOR for the lowest temperature assessed (205°C). For MOE, the 22% reduction was much higher than the 5% to 6% found by Menezes (2017), while Lengowski et al (2021) reported an increase of 24%.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…This has led some researchers to study the suitability of TM to darken and homogenize the color of teak wood from short-rotation plantations as a means of its valorization [14,15]. Since color is one of the most important wood properties for the wood market, other authors also studied the effect of TM on the teak wood color [16][17][18][19][20][21]. However, the majority of the studies used open-system processes [15][16][17][18][19][20], whereas few studies used different processes, such as thermo-vacuum [14] and pressurized closed systems [21].…”
Section: Introductionmentioning
confidence: 99%
“…Since color is one of the most important wood properties for the wood market, other authors also studied the effect of TM on the teak wood color [16][17][18][19][20][21]. However, the majority of the studies used open-system processes [15][16][17][18][19][20], whereas few studies used different processes, such as thermo-vacuum [14] and pressurized closed systems [21].…”
Section: Introductionmentioning
confidence: 99%